2019
DOI: 10.1108/apjml-10-2018-0448
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the technology acceptance model for mobile commerce adoption under distinct stages of adoption

Abstract: Purpose The purpose of this paper is to investigate the role of trust and perceived enjoyment in the technology acceptance model by distinguishing distinct stages of adoption among street vendors (initial and advanced adoption stage). Design/methodology/approach Face-to-face interviews using a structured questionnaire were conducted with 430 street vendors in Bangkok; 415 usable surveys were analyzed. By applying K-means cluster analysis, two segments were found with 200 initial and 215 advanced adopters. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 88 publications
5
39
0
1
Order By: Relevance
“…Here we take perceived trust as an overall concept of weakening the uncertainty about downloading the paid Apps and playing positive roles in the final decision-making. Many other researchers have indicated that trust perception in m-commerce is much more prominent than in traditional commerce (Corbitt et al, 2003;Cho et al, 2007;Shin, 2009;Zhou, 2013), and have shown that trusting beliefs lead to users' behavioral intentions (Benbasat and Wang, 2005;Zhang et al, 2012;Pipitwanichakarn and Wongtada, 2019). Hence, we hypothesize:…”
Section: Perceived Trustmentioning
confidence: 95%
“…Here we take perceived trust as an overall concept of weakening the uncertainty about downloading the paid Apps and playing positive roles in the final decision-making. Many other researchers have indicated that trust perception in m-commerce is much more prominent than in traditional commerce (Corbitt et al, 2003;Cho et al, 2007;Shin, 2009;Zhou, 2013), and have shown that trusting beliefs lead to users' behavioral intentions (Benbasat and Wang, 2005;Zhang et al, 2012;Pipitwanichakarn and Wongtada, 2019). Hence, we hypothesize:…”
Section: Perceived Trustmentioning
confidence: 95%
“…These SMEs utilized basic electronic devices such as smartphones, laptops, and desktop for general usages like social networking and business information management. As indicated by Pipitwanichakarn and Wongtada (2019), this type of user is considered as late majority IoT category due to their low usage of electronic devices. The remaining 79 (50%) halal agro-food SMEs were categorized as a high rate of electronic devices utilization which also considered as early adopters of IoT as they demonstrated the presence of smart devices and highly utilized those devices in managing their business activities.…”
Section: Methodsmentioning
confidence: 99%
“…Based on the SLR and experts' evaluation, the factors screened were exactly the Rogers' five technological factors (Relative advantage, Complexity, Compatibility, Trialability, and Observability -see Table 3 for the definitions). According to Banapour et al (2020) and Pipitwanichakarn and Wongtada (2019), the factors in Rogers (2003) theory of diffusion of innovation (DOI) are the most commonly studied factors used to examine the impact of technological factors on technology adoption by SMEs. Many studies used these technological characteristics as a criteria for determining the level of IT adoption in a business (Karunagaran et al, 2019;Khayer, Talukder et al, 2020;Ma & Lee, 2019; S. Z.…”
Section: Technology Characteristicsmentioning
confidence: 99%